A new mutual coupling compensation method for receiving antenna array-based DOA estimation - Naser Parhizgar (Archives of Electrical Engineering, 2018)
Most receiving antenna arrays suffer from the mutual coupling problem between antenna elements, which can critically influence the performance of the array. In this work, a novel and accurate form of compensation matrix is applied to compensate the mutual coupling in a uniform linear array (ULA). This is achieved by applying a new method based on solving a boundary value problem for the whole ULA. In this method, both self and mutual impedances are exploited in an accurate characterization of mutual impedance matrix which results in a perfect mutual coupling compensation method, and hence a very accurate direction of arrival (DOA) estimation. In the new scheme, the compensation ma- trix is obtained by using the relationship between measured voltage and theoretical coupled voltage based on the MOM. Numerical results show that using DOA estimation algorithms to the decoupled voltage obtained by using this method leads to an excellent performance of DOA estimation with higher accuracy and resolution.